Terahertz nanofuse by a single nanowire-combined nanoantenna - Choi Geunchang; Roh Yeeun; Seo Minah (Nanophotonics)
We propose a terahertz nanofuse through irreversible modulations in transmitted terahertz using nanowires-combined nanoantenna structures. Semiconductor and metal nanowires show irreversible reconfiguration in their geometry at an incident field of 20 kV/cm. The concept can be explained by terahertz-field-induced ionization or electromigration. A strongly localized field due to geometrical conditions causes a floated metal nanowire from one side of a metal nanoantenna to touch the opposite side, bridging two separate metal plates and creating a junction. For the bridged nanoantenna, the highly enhanced field induced the breaking of the connection across the metal sides of a nanoantenna. In the bridging and breaking cases, permanent transformation occurs in opposite structural forms. It encompasses a potential application as an optical fuse to protect sensitive terahertz devices under excessive field focus.